How does the ERAS protocol work in patients who underwent cesarean section? (HERMES study) - Özgün Uyanıklar, Özlem; Türk, Pınar; Aslan, Kiper; Külahçı Aslan, Elif; Özden, Okan; Gürlüer, Jale; Orhan, Orhan; Vural, Nazlı Aylin; Kılık, Tuğba; Kasapoğlu, Işıl; Uncu, Gürkan (John Wiley and Sons Ltd, 2023)
Objective To assess the effect of the enhanced recovery after surgery (ERAS) protocol for cesarean deliveries (CD) on postoperative outcomes. Methods This multicenter prospective cohort study was conducted in six different centers between September 2020 and March 2021 and involved women who underwent either planned or unplanned CD. The primary outcome was time to the first passage of flatus following CD. Secondary outcomes included postoperative pain score, postoperative complications, and patient satisfaction. The protocol included early postoperative oral intake of ice cream and coffee, multimodal analgesia, antiemetic medications, and early ambulation. Results A total of 448 patients were included. The median time to the first passage of flatus was 10 h in the Hermes group and 18 hours in the control group (P < 0.001). Postoperative visual analog scale scores were significantly higher in the control group. Patient satisfaction scores and the frequency of postoperative complications did not differ between the groups (P = 0.08, P = 0.604, respectively). Conclusions The ERAS protocol, including early serving of ice cream and coffee in the early postoperative period, enabled early discharge and a faster return of bowel function. Implementation of the ERAS protocol for patients who underwent planned and unplanned CD appeared to be safe and effective.
Keywords: Cesarean Delivery; Enhanced Recovery After Surgery; Maternal Outcomes